Melatonin Protects Cultured Tobacco Cells against Lead-Induced Cell Death via Inhibition of Cytochrome c Translocation - Kobylińska, Agnieszka; Reiter, Russel J.; Posmyk, Malgorzata M. (Frontiers in Plant Science, 2017)
Melatonin was discovered in plants more than two decades ago and, especially in the last decade, it has captured the interests of plant biologists. Beyond its possible participation in photoperiod processes and its role as a direct free radical scavenger as well as an indirect antioxidant, melatonin is also involved in plant defense strategies/reactions. However, the mechanisms that this indoleamine activates to improve plant stress tolerance still require identification and clarification. In the present report, the ability of exogenous melatonin to protect Nicotiana tabacum L. line Bright Yellow 2 (BY-2) suspension cells against the toxic exposure to lead was examined. Studies related to cell proliferation and viability, DNA fragmentation, possible translocation of cytochrome c from mitochondria to cytosol, cell morphology after fluorescence staining and also the in situ accumulation of superoxide radicals measured via the nitro blue tetrazolium reducing test, were conducted. This work establishes a novel finding by correcting the inhibition of release of mitochondrial ctytocrome c in to the cytoplasm with the high accumulation of superoxide radicals. The results show that pretreatment with 200 nm of melatonin protected tobacco cells from DNA damage caused by lead. Melatonin, as an efficacious antioxidant, limited superoxide radical accumulation as well as cytochrome c release thereby, it likely prevents the activation of the cascade of processes leading to cell death. Fluorescence staining with acridine orange and ethidium bromide documented that lead-stressed cells additionally treated with melatonin displayed intact nuclei. The results revealed that melatonin at proper dosage could significantly increase BY-2 cell proliferation and protected them against death. It was proved that melatonin could function as an effective priming agent to promote survival of tobacco cells under harmful lead-induced stress conditions.